Early recognition of anti-N-methyl D-aspartate (NMDA) receptor encephalitis presenting as acute psychosis. (December 2013) - Tidswell, Jessica; Kleinig, Timothy; Ash, David; Thompson, Philip; Galletly, Cherrie
Objective: We present a case of anti-N-methyl D-aspartate (NMDA) receptor encephalitis that illustrates the dilemma that psychiatrists face in evaluating patients with first episode psychosis. Conclusions: The discovery that acute psychosis can be the presenting feature of autoimmune encephalitis (in particular encephalitis caused by anti-NMDA receptor antibodies) has both practical and theoretical consequences. First, this condition is an important, but often overlooked, differential diagnosis of first episode psychosis. Antibody testing is not currently part of routine screening, though delayed (or missed) diagnosis can lead to prolonged hospital stay, medical complications and incomplete or delayed recovery. Widespread screening of patients with first presentation psychosis for anti-NMDA receptor and anti-voltage-gated potassium channel (anti-VGKC) antibodies is warranted for a number of reasons: to expedite appropriate treatment, to determine the true proportion of patients with these conditions presenting as psychosis, and to help elucidate the neurochemical causes of psychosis.